Effects of Zn2SiO4 on the phase evolution, thermal expansion and mechanical properties of LiAlSiO4 ceramic. Issue 16 (November 2018) - Hao, Liang; Ren, Haishen; Peng, Haiyi; Zhang, Yi; Meng, Fancheng; Yao, Xiaogang; Lin, Huixing
Abstract: LiAlSiO4 (abbreviated as LAS) ceramics doped with variable mass percent of Zn2 SiO4 were prepared by conventional solid-state route. The effects of Zn2 SiO4 on the phase evolution, microstructure, thermal expansion and mechanical properties have been fully investigated. The results show that Zn2 SiO4 reacted with LAS matrix to produce Li2 Al2 Si3 O10 and ZnAl2 O4 . Fine-grain ZnAl2 O4 phase accumulated on the grain boundaries of the main phase, which was helpful to improve the density. Simultaneously, both of the flexure strength and Vickers hardness of the multiphase ceramics were significantly enhanced with the increasing mass percent of Zn2 SiO4 for the reason of dispersion strengthening effect. In addition, when the content of Zn2 SiO4 increased from 10 wt% to 22.5 wt%, the coefficient of thermal expansion (CTE) of the composite ceramics increased monotonously from − 5.24 × 10 −6 /K to 1.49 × 10 −6 /K. Typically, the LAS ceramic doping with 17.5 wt% Zn2 SiO4 sintered at 1175 °C for 4 h possesses excellent properties: α = 0.65 × 10 −6 /K, Hv = 5.34 GPa, σs = 102.6 MPa, which is a promising material in laser gyroscope and precision machining fields.